2014
DOI: 10.1128/mbio.01133-14
|View full text |Cite
|
Sign up to set email alerts
|

Altered Oral Viral Ecology in Association with Periodontal Disease

Abstract: The human oral cavity is home to a large and diverse community of viruses that have yet to be characterized in patients with periodontal disease. We recruited and sampled saliva and oral biofilm from a cohort of humans either periodontally healthy or with mild or significant periodontal disease to discern whether there are differences in viral communities that reflect their oral health status. We found communities of viruses inhabiting saliva and the subgingival and supragingival biofilms of each subject that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
221
1
8

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 160 publications
(234 citation statements)
references
References 83 publications
4
221
1
8
Order By: Relevance
“…Those studies have demonstrated that viral communities are highly diverse, carry substantial pathogenic gene functions, are populated by viruses that persist over time, and have individual- and body surface-specific ecology [1, 36, 12, 20]. Our data indicate that viral communities in the mouth and gut are readily shared within a household, likely through transmissions from one subject to another.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Those studies have demonstrated that viral communities are highly diverse, carry substantial pathogenic gene functions, are populated by viruses that persist over time, and have individual- and body surface-specific ecology [1, 36, 12, 20]. Our data indicate that viral communities in the mouth and gut are readily shared within a household, likely through transmissions from one subject to another.…”
Section: Discussionmentioning
confidence: 57%
“…How the microbiome responds to perturbations such as antibiotics may determine our susceptibility to pathogen colonization and/or to the development of certain diseases [68]. Viral communities also respond to perturbations, although in different ways than might be predicted based on the responses of their bacterial hosts.…”
Section: Introductionmentioning
confidence: 99%
“…As major technical advancements have brought the human virome to light, several critical and unanticipated observations have been described. It is now known that healthy humans carry a large diversity of both eukaryotic viruses and prokaryotic phages [1719]. Furthermore, human blood, once thought to be sterile in healthy individuals, was found to contain both virus and phage [17, 20].…”
Section: From Reductionism To Holism: Systems-level Understanding Of mentioning
confidence: 99%
“…Bacteriophages share with host bacteria a similar site-specific diversity in the mouth and disease associations such as periodontitis[220,221]. Other viruses, such as HIV, also alter the oral microbiome, mycobiome, and NO-driven disease susceptibility (such as CVD and PH)[222224].…”
Section: The Oral Microbiome and Bacterial Nitrate Reductionmentioning
confidence: 99%